SEBUAH STUDI TERHADAP STRATEGI-STRATEGI BELAJAR YANG DIGUNAKAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP UNIVERSITAS RIAU TAHUN KE 2 DALAM BELAJAR BAHASA INGGRIS - Warahmah, Mawaddah; Ras, Fakhri; ', H.M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this descriptive research was to describe the students’ Language Learning Strategies in learning English. The population of this research was the second year students of English study program of FKIP Universitas Riau of 2014/2015 academic year. The whole number of the population is about 86 students. Due to the large population which is consisting of 3 classes, the random sampling technique is used. One of the classes is taken as the sample as many as 30 students. The adopted from SILL questionnaire (Strategy Inventory for Language Learning) version 7.0 is used to collect the data. The collected data were analyzed by calculating the scores of the students in answering the questionnaire and classified them to a certain level of SILL Profile of Result. The research finding can briefly explain as follows: First the result of the SILL shows that, the most often Language Learning Strategies used by the students is the Compensation strategies with mean score 3.90 (classified as High level). Then, the less frequent used strategies by the students is Memory Strategies with mean score 3.22 (classified as Medium level). This means that the students were very good in guessing intelligently in listening and reading but not too well in remembering when they are learning English. The suggestion is it would be better if they also can use the other strategies which are appropriate to their tasks, difficulties and learning objectives. Then, hopefully students can improve their English by using more language learning strategies in their learning to help learning easier, and enjoyable.Keywords: language leaning strategy, learning, English